Detection of Suspected Placental Invasion by MRI - A Prospective Study in a Tertiary Care Hospital (Medical Forum Monthly, 2024)
Objective: To evaluate the diagnostic value of MRI features used for detecting suspected placental invasion.Study Design: Prospective / Observational studyPlace and Duration of Study: This study was conducted at the Radiology Department Liaquat National Hospital and Medical College, Karachi June 2015 to December 2017.Materials and Methods: All the patients referred to MRI department for the evaluation of placental invasion over 18 months and then went for surgery were included in the study. MRI images of all the patients who met the inclusion criteria were evaluated for placental invasion according to the established MR criteria and the findings were correlated with surgical findings.Results: Total 9 patients met the inclusion criteria with a mean gestational age of 32 weeks. All of these patients had placenta previa and history of multiple previous C-sections. Placental invasion was proven (both surgically and pathologically) in 5 cases (55%). Out of which 3 had pathologically proven increta (60%), one had pathologically proven accreta (20%) and one had pathologically proven percreta (20%). MR evaluation of these patients showed focal interruption of myometrial band, thick intra-placental bands, heterogenous signal intensity of placenta and focal uterine bulging. The MR features of 4 non-invasive placentas include prominent flow voids on fetal and maternal surface of placenta and focal interruption of retro-placental myometrial border. One of the patient had thin intra-placental band.Conclusion: We found that focally interrupted myometrial border was found to be the least sensitive MR feature. Thick intra-placental bands, heterogenous placental signal intensity and disorganized intra-placental vessels were the sensitive MR features for invasion.